The Position of General Principles of Law in the Interpretation of Treaties - Hajjar, Mahmoud; Zamani, Seyed Ghasem (Public Law Researsh, 2023)
The interpretation of treaties is particularly important in the field of treaty law, as in most cases it is not possible to apply treaties without their interpretation. In addition to the text and context of the treaty, the relevant rules of international law, including the general principles of law, can play an important role in the interpretation of treaties. A treaty is a creation of the international legal system, and its interpretation and implementation should be carried out within the context of the legal system that governs it. The main question to which this research intends to answer is: What is the position of general principles of law in the interpretation of treaties? It seems that the use of general principles of law in the interpretation of treaties can reduce the potential fragmentation of international law and promote its coherence. In this research, by using library sources, international documents and international judicial decisions and arbitration awards and using a descriptive-analytical method, the position of general principles of law in the interpretation of treaties will be examined.
Keywords: Article 31 (3) (C) of the Convention of the Law of Treaties; General Principles of Law; International Jurisprudence; Interpretation of Treaties; Systemic Integration